PENGARUH NON PERFORMING FINANCING (NPF) DAN FINANCING TO DEPOSIT RATIO (FDR) TERHADAPRETURN ON ASSETS (ROA) DI PT. BANK JABAR BANTEN SYARIAH KANTOR PUSAT - Lenny Yanthiani (Universitas Widyatama, 2019)
This research is motivated by the increasingly critical of Islamic banking customers choose a bank that is performing well. PT. Bank Jabar Banten Islamic one public option bank seeks to provide optimum advantages and benefits to customers and stakeholders. The purpose of this study is to determine how influential NPF on ROA, FDR on ROA and simultaneously NPF and FDR on ROA. It is very important to study because it is one of the indicators in knowing the level of business development at BJB Bank Syariah. As we all know, that the development of good business then it will be good also profit to be generated bank. This will have an impact on the trust and loyalty of customers in the store and transact funds in Bank BJB sharia, automatically perusahanakan business performance the better. The management and shareholders increasingly believe and do not hesitate to invest. The existing framework in this study are the theories related to the NPF, FDR and the ROA, which in theory is explained among other NPF influence on ROA, FDR influence on ROA and simultaneously influence the NPF and the FDR on ROA. This research method when viewed from the goal included in the study causative (causative) is to analyze the influence of some variable to another variable. Say so, because this study connects the three (3) variables, namely NPF and FDR as an independent variable (independent variable, the statistical notation X) while the ROA as the dependent variable (the dependent variable, the statistical notation Y). Based on the results of the study concluded that: Changes or variations achievement ROA value is affected by changes or variations of NPF and FDR, although only 10.70%, but very significant ; NPF significantly negative effect on ROA with significant regression coefficient that is equal to -0.019 or -1.90% and sig-t coefficient of 0.0075; The effect of FDR on ROA despite having the appropriate regression toward the hipotesi statement, but the regression coefficient of 0.0003 obtained is not significant.